TIMP1 inhibits Rac1-mediated ROS production to ameliorate blood–spinal cord barrier disruption in amyotrophic lateral sclerosis - Jingshu Tang; Yuying Kang; Qiuyu Chen; Baodan Zhang; Nianying Shang; Jiaqi Lan; Lei Wu; Ying Peng (Neurobiology of Disease)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder characterized by the progressive degeneration of motor neurons, for which therapeutic strategies and pharmacological interventions remain limited. Disruption of the blood–spinal cord barrier (BSCB) has been identified as a significant factor that may exacerbate motor neuron damage. Tissue inhibitor of metalloproteinase-1 (TIMP1), a molecule known for its dual roles in inhibiting matrix metalloproteinase (MMP) activity and exerting cytokine-like effects via receptor interactions, has been demonstrated to ameliorate endothelial barrier damage in various diseases. Here, we explored the potential of TIMP1 to restore BSCB integrity as a strategy to slow the ALS progression. Specifically, the expression of TIMP1 or its mutant variant AlaTIMP1, which lacks MMP-inhibitory activity, in spinal cord microvascular endothelial cells (SCMECs) prior to disease onset significantly reduces BSCB leakage in mice with ALS, thereby alleviating motor function deficits and delaying disease progression. Additionally, TIMP1 expression restores the expression of junctional complexes in SCMECs, as demonstrated in both in vivo and in vitro ALS models. Mechanistic studies revealed that TIMP1 suppresses ALS injury-induced integrin β1 activation independent of MMP inhibition, blocking downstream Rac1 translocation to the membrane to form a complex with NOX2. The inhibition of NOX2 activity reduces ROS-induced cytoskeletal remodeling, consequently stabilizing overall junctional alignment and preserving the BSCB integrity. Overall, our findings elucidate an MMP-independent mechanism through which TIMP1 regulates BSCB integrity in ALS context, suggesting that TIMP1 could serve as a novel tool for the treatment of ALS, particularly for prophylactic treatment in patients with familial ALS.